ANALISIS KEBIJAKAN RASKIN TERHADAP KETAHANAN PANGAN RUMAH TANGGA DI KABUPATEN TAKALAR (STUDI KASUS DESA PARANGBADDO KECAMATAN POLONGBANGKENG UTARA) - Jam'ah, Andi; Asdar, Asdar; Pratiwi, Pratiwi (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
This study aims to explain the process of distributing Raskin to low income communities in the village of Parangbaddo Kecamatan Polongbangkeng Utara Takalar District. The study used a descriptive qualitative approach with the Raskin program as an analysis unit. Data sources consist of primary data obtained through observation, interviews and documentation and secondary data obtained through intermediary media in the form of books, notes, or archives related to problems in research. The results showed that the Raskin distribution process was carried out through regional administration channels. in Takalar Regency, through the South Sulawesi Provincial Government, Takalar District Government, North Polongbangkeng Sub-District, then the Parangbaddo Village / Sub-district until finally it can be channeled directly to the community.